Mechanical and physical characterization of chemically treated corncob fiber reinforced polyester bio-composite - Muhamad Afiq Rosli (2024)
The research for sustainable materials has lead top the exploration of bio-composites, such as corn cob fiber (CCCF) reinforced unsaturated polyester resin (UPR), for various application. Corn cob fiber (CCF) reinforced unsaturated polyester resin (UPR) bio-composites have been prepared using hand lay-up and compression moulding technique. To improve fiber matrix adhesion, the CCF was chemically treated with 2%, 4%, 6% and 8% alkaline solution that is sodium hydroxide (NaOH) at the same soaking time 3 hours to enhance the interfacial bonding between the fiber and matrix.. Fourier transform infrared (FTIR) was used to investigate the changes of fibers chemical constituencies and thermal behaviour after alkaline treatment. Mechanical properties such as tensile strength, tensile modulus and elongation at break of untreated and NaOH treated CCF/UPR bio-composites were also studied and compared. The incorporation of the alkaline CCF resulted in composites better tensile properties and 4% treated showed the best result. Thermal stability of the CCF/UPR bio-composites were significantly enhanced after alkaline treatment compared to those of untreated CCF/UPR bio-composites. Thus the chemical treatment on CCF improved fiber-matrix adhesion, which also contributed to the improvement of mechanical properties compared to those of untreated CCF/UPR bio composites.